Comparing apples with apples: A proposed taxonomy for "Community Health Workers" and other front-line health workers for international comparisons. - Stephen Hodgins; Uta Lehmann; Henry Perry; Nicholas Leydon; Kerry Scott; Smisha Agarwal; Hannah Marcus; Rajani Ved; Elijah Olivas; Madeleine Ballard; Dickson Mbewe; Margaret Odera; et al. (PLOS Global Public Health)
This paper proposes a taxonomy for Community Health Workers (CHWs) and others engaged in front-line community health activities, encompassing formally-employed workers extending government primary health care (PHC) service delivery as well as a range of other actors with roles at the nexus of government PHC and communities. The taxonomy is grounded in current definitions from the World Health Organization and the International Labor Organization, and proposes some refinements for future iterations of guidance from these agencies. The designation, "Community Health Worker" is currently used to cover a broad range of roles. Furthermore, there are programs engaging workers or community members in roles closely adjacent to those generally recognized as CHWs that use other designations, not commonly included under the rubric of "CHW". This potentially confusing range of roles and nomenclature leads at times to over-generalizations, applying insights and principles relevant for one type of worker or community member that are not necessarily relevant for another. It also leads to a failure to consider occupational groups not commonly thought of as CHWs-but engaged in PHC service delivery at the most peripheral level-in community-based-PHC planning and management arrangements. Building on ILO and WHO classifications and standards, a further clarification of terms and a taxonomy is proposed, with the intention of contributing to clearer communication and shared understanding and, ultimately, sounder community health policy, program planning, and implementation; and more substantial progress towards Universal Health Coverage.